Ultra-High Tg Thermoset Fibers Obtained by Electrospinning of Functional Polynorbornenes - Basile Commarieu; Moubarak Compaoré; Raphaël de Boëver; Régis Imbeault; Maxime Leprince; Barbara Martin; Bruno Perard; Weiguang Qiu; Jerome P. Claverie (Nanomaterials, 2022)
Insertion polynorbornenes (PBNEs) are rigid-rod polymers that have very high glass transition temperatures (Tg). In this study, two functional PNBEs were electrospun in the presence of a variety of cross-linkers, resulting in fibers with Tgs greater than 300 °C. The fibers are long (several mm), rigid, and with diameters that can be tuned in the range 300 nm–10 μm. The electrospinning process can be used to encapsulate dyes or graphene dots. Due to the high cross-linking density of the fiber, dye leaching is prevented. In contrast with other rigid-rod polymers, electrospinning of PNBE is facile and can be performed at injection rates as high as 1 mL/min.